2016
DOI: 10.1016/j.eurpsy.2015.09.461
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-reactive protein levels in schizophrenia inpatients is associated with aggressive behavior

Abstract: This study identified a potential biological correlate (inflammation) of a specific behavioral endophenotype (aggression) in schizophrenia inpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
7
36
0
2
Order By: Relevance
“…We have recently reported an association between elevated CRP and excitement/agitation using the PANSS-EC scale, in non-affective psychotic schizophrenia inpatients from the same inpatient unit [12]. Therefore, we wanted to exclude the possibility that the increased CRP levels may be accounted for by the increased excitement component, which was observed in the manic patients (results section Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported an association between elevated CRP and excitement/agitation using the PANSS-EC scale, in non-affective psychotic schizophrenia inpatients from the same inpatient unit [12]. Therefore, we wanted to exclude the possibility that the increased CRP levels may be accounted for by the increased excitement component, which was observed in the manic patients (results section Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…PANSS score was determined by the patient’s treating psychiatrist following an interview that was conducted within 72 h from admission as a routine practice of the inpatient unit. PANSS excitement component (PANSS-EC) was used as a measure of excitement/agitation [12]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research groups have found a positive association between elevated CRP levels and Framingham risk score (Sicras-Mainar et al, 2013), whereas other reports did not observe a significant association (Joseph et al, 2015). In schizophrenia, both CRP and Framingham risk have been linked to higher body mass index (BMI) (Miller et al, 2014; Joseph et al, 2015), psychiatric symptom severity (Barzilay et al, 2016; Dimitrov et al, 2016), and other dysregulated metabolic factors including fasting glucose and hemoglobin A1c levels (Dieset et al, 2012; Joseph et al, 2015). A correlation between CRP levels and routinely prescribed antipsychotic medication treatments has also been observed by some groups (Stefanovic et al, 2015).…”
Section: Schizophrenia and Cardiovascular Diseasementioning
confidence: 99%
“…[8][9][10] Inflammation, as a marker for psychopathological symptoms and disorders, is of emerging interest due to recent preclinical and clinical information proposing a significant clinical connection. 11 Information regarding the role of CRP as a low-grade inflammation marker in psychiatric disorders is still contradictory. Nonetheless, a few studies have highlighted the connection between some psychiatric disorders, for example, depression, bipolar disorder and schizophrenia and raised CRP levels.…”
Section: Introductionmentioning
confidence: 99%